High-resolution light-activated electrochemistry on amorphous silicon-based photoelectrodes. Issue 54 (3rd June 2020) - Gautam, Shreedhar; Gonçales, Vinicius R.; Colombo, Rafael N. P.; Tang, Wenxian; Córdoba de Torresi, Susana I.; Reece, Peter J.; Tilley, Richard D.; Gooding, J. Justin
Abstract : The spatial resolution of silicon photoelectrochemistry is improved to 500 nm by using amorphous silicon, 60 times improvement as compared to crystalline silicon. Abstract : Light-activated electrochemistry (LAE) consists of employing a focused light beam to illuminate a semiconducting area and make it electrochemically active. Here, we show how to reduce the electrochemical spatial resolution to submicron by exploiting the short lateral diffusion of charge carriers in amorphous silicon to improve the resolution of LAE by 60 times.